2005
DOI: 10.1111/j.1464-410x.2005.05684.x
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of risk factors in men with chronic pelvic pain syndrome

Abstract: OBJECTIVETo compare the demographic, behavioural, clinical and medical history characteristics of men with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and asymptomatic controls, to identify characteristics that might be associated with this syndrome. PATIENTS AND METHODSSelf-administered epidemiological questionnaires were completed by 463 men with CP/CPPS and 121 asymptomatic agematched controls. We compared the prevalence of possible risk factors between men with CP/CPPS and controls, using ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 24 publications
(20 reference statements)
4
62
0
4
Order By: Relevance
“…Various complex causes (urinary tract infection, prostatic urinary tract counterflow [9], Cytokines [10], pelvic floor spasm [11], systemic nervous or endocrine cause [12] and neuropsychiatric cause [13]) affects CP/CPPS in terms of pathological physiology (Fig. 1).…”
Section: Cause Of Cp/cppsmentioning
confidence: 99%
“…Various complex causes (urinary tract infection, prostatic urinary tract counterflow [9], Cytokines [10], pelvic floor spasm [11], systemic nervous or endocrine cause [12] and neuropsychiatric cause [13]) affects CP/CPPS in terms of pathological physiology (Fig. 1).…”
Section: Cause Of Cp/cppsmentioning
confidence: 99%
“…Patients with UCPPS have a high incidence of concomitant, but associated medical conditions that are often pain related or have features of autonomic dysfunction, as well as peripheral and central nervous system sensitization (neuropathic). 24 These include irritable bowel syndrome, fibromyalgia, Clinical phenotyping in CP/CPPS and IC DA Shoskes et al vulvodynia, chronic fatigue syndrome, migraine headaches and low back/leg pain. These patients are phenotyped into the neurological/systemic phenotype by good history taking supplemented by physical examination.…”
Section: Clinical Phenotypingmentioning
confidence: 99%
“…Men with CP/CPPS were 5 times more likely to self-report a history of nervous system disease, as compared to asymptomatic age-matched controls in the CPCRN Study [18].…”
Section: Nervous Systemmentioning
confidence: 99%
“…However, studies that have looked for the presence of sexually transmitted organisms such as Chlamydia trachomatis, Trichomonas vaginalis, Ureaplasma urealyticum, or Mycoplasma hominis have failed to show persistent infection [17]. Although the presence of an active infection was not evident in men participating in the National Institutes of Health (NIH) cohort study, patients with CP/CPPS were found to have a significantly greater history of urethritis, as compared to age-matched controls [18]. In susceptible men, urethritis could serve as a source of inflammation that could cause chronic pelvic pain well after the resolution of infection.…”
mentioning
confidence: 93%